KEMASAN DAN PEMASARAN KELOMPOK ORGEN TUNGGAL “PINK MUSIK”: Suatu Tinjauan Manajemen Seni Pertunjukkan - Yoni Sesilia; Indrayuda Indrayuda; Tulus Handra Kadir (SENDRATASIK UNP, 2013)
Abstract This article aimed at describing the production management of Pink Music Group and explaining its music shows marketing system. The object of this research was the Pink Music Group. The data were obtained from observation, literature review, interview, and documentation. The data were analyzed by using the phenomenology analysis technique. The data showed that Pink Music Group organized its activities by using the production management and its marketing by using the managerial science approach specializing in music shows   Keywords : Pink Music Group’s, Marketing, and Music Show   Management.